Board interlocking: o impacto das conexões com instituições financeiras no custo de capital de terceiros e no nível de endividamento das empresas listadas na B3 - Bampi, Jéssica Krewer (Universidade do Vale do Rio dos Sinos, 2022)
Previous studies have shown the importance of centrality and the financial services sector within board interlocking. It makes it relevant to analyze the effects of the connections between board members and financial companies to identify agency conflicts or even if the directors properly perform the role to protect shareholders' interests. This study aims to evaluate the relationship between board members and financial companies by assessing its effects on indebtedness and capital cost of non-financial companies. To do so, we collected data from Brazilian companies listed on B3 from 2011 to 2020. Considering that the research's primary goal is to verify if board interlocking with financial companies can affect indebtedness and capital cost in Brazilian non-financial companies, our sample comprises some banks to map and measure the networks but drop them out, econometric models. We used ordinary least squares (OLS) to test the research hypotheses. We also estimated robustness tests to confirm our findings and guarantee data reliability, considering additional board interlocking measures between financial and non-financial companies. Our results show that when non-financial companies relate to financial companies, they have their capital cost and indebtedness decrease. However, the capital cost is affected only by the direct connections with financial companies; meanwhile, the indebtedness is affected by direct and indirect connections. Besides that, our findings show that dry liquidity does not moderate the interlocks' effect with financial companies on indebtedness. These research findings contribute to the literature by applying agency and dependency resources theories and contributing to the corporate finance field by proving that board interlocking with financial companies can impact company value, measured by indebtedness and cost capital.
Keywords: Board interlocking; Redes de conexão; Instituições financeiras; Endividamento; Custo de capital de terceiros; Social networks; Financial companies; Indebtedness; Cost capital; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis